GCG Effect and CSR of Sharia Banking in Indonesia - Soliyah Wulandari; Asep Dadan Suganda (Basic and Applied Accounting Research Journal, 2022)
This study aims to prove empirically the effect of good corporate governance on corporate social responsibility, in which good corporate governance refers to the audit committee, board independence, government ownership, and institutional ownership. The object of this research was Islamic Commercial Banks, mostly owned by State-Owned Enterprises (BUMN) or Regional-Owned Enterprises (BUMD). The sample selection was carried out using the purposive sampling method. Based upon the sample criteria applied in this study, there were six Islamic banks with 30 observations. The secondary data was collected from the annual report of the six Islamic banks. The data was processed using a statistical test of multiple regression models. The results of this study indicate that board independence and government ownership affect the corporate social responsibility of Islamic banking in Indonesia. Meanwhile, the audit committee and institutional ownership did not affect the corporate social responsibility of Islamic banking in Indonesia